2012
DOI: 10.1186/1471-2458-12-476
|View full text |Cite
|
Sign up to set email alerts
|

The association between travel time to health facilities and childhood vaccine coverage in rural Ethiopia. A community based cross sectional study

Abstract: BackgroundFew studies have examined associations between access to health care and childhood vaccine coverage in remote communities that lack motorised transport. This study assessed whether travel time to health facilities was associated with childhood vaccine coverage in a remote area of Ethiopia.MethodsThis was a cross-sectional study using data from 775 children aged 12–59 months who participated in a household survey between January –July 2010 in Dabat district, north-western Ethiopia. 208 households were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
72
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(82 citation statements)
references
References 19 publications
9
72
1
Order By: Relevance
“…In Ethiopia the acceptability of distance to services differed based on the time-intensiveness of other domestic responsibilities such as fetching water and caring for cattle or other family members. Other evidence from rural Ethiopia further highlights the critical implications of distance barriers, showing that children living more than 1·5 h from a health centre (but not from health posts) have a two to three times greater risk of death than those living closer (27) and that travel time is significantly associated with coverage of important childhood vaccines (28) . Both of these Ethiopian studies suggest that households in remote rural areas are more vulnerable to the distance barrier compared with those in more densely populated areas.…”
Section: Discussionmentioning
confidence: 99%
“…In Ethiopia the acceptability of distance to services differed based on the time-intensiveness of other domestic responsibilities such as fetching water and caring for cattle or other family members. Other evidence from rural Ethiopia further highlights the critical implications of distance barriers, showing that children living more than 1·5 h from a health centre (but not from health posts) have a two to three times greater risk of death than those living closer (27) and that travel time is significantly associated with coverage of important childhood vaccines (28) . Both of these Ethiopian studies suggest that households in remote rural areas are more vulnerable to the distance barrier compared with those in more densely populated areas.…”
Section: Discussionmentioning
confidence: 99%
“…A few studies also identified household income, child illness [19, 20], poor male partner involvement [15], and large family size [16] to be associated with defaulting. Incomplete immunization is also commonly linked to weaknesses in the health systems, such as the lack of vaccines during vaccination sessions [17] and poor geographic access and long distance from the sites [7, 8, 12, 15, 21], including in urban settings [13]. Poor service arrangements with long waiting time [13, 15], inconvenient schedules [16], unwelcoming health care environment [16, 19], and not holding sessions as planned [22] were also mentioned.…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, outreach vaccination programs have been used in low‐ and middle‐income countries. Some communities in these countries frequently have difficulty accessing vaccines due to geographical barriers to healthcare facilities 25–27 . Since early 2000, the World Health Organization advocated using the ‘Reaching Every District’ (RED) strategy to reach out to under‐served, un‐reached communities 28 .…”
Section: Discussionmentioning
confidence: 99%
“…Some communities in these countries frequently have difficulty accessing vaccines due to geographical barriers to healthcare facilities. [25][26][27] Since early 2000, the World Health Organization advocated using the 'Reaching Every District' (RED) strategy to reach out to under-served, un-reached communities. 28 This has been successfully rolled out in certain countries.…”
Section: Discussionmentioning
confidence: 99%